Assessment of degree of willingness to undergo covid test amongst the patients visiting SDM college of dental sciences & hospital, Dharwad - Bhat, Pragathi R; Bolar, Pratheek; Trasad, Vijay A (Journal of Dental Panacea, 2021)
Severe Acute Respiratory Syndrome Coronavirus-2 or SARS-CoV-2 is a deadly pandemic sickness that is currently affecting throughout the globe and the need of the hour is that people become aware about the contagious disease, and are willing to undergo the Covid-19 test as an when needed. : To assess the degree of willingness to undergo covid test amongst patients visiting SDMCDSH, Dharwad. : A questionnaire with 15 questions pertaining to their willingness to undergo a covid test was assessed in 332 participants. A pre-tested close ended questionnaire comprising of 15 questions were distributed to 332 patients between 18-65 years of age visiting outpatient department of SDMCDSH, Dharwad with questions related to willingness of the participants to undergo COVID-19 test. A Pearson’s Chi Square value using an SPSS software was used to assess the differences in the gender, level of education and occupation of all the subjects. A statistically significant p-value was set as < 0.05. Majority of the study participants had a positive attitude towards covid test and were willing to undergo the test as and when needed thus concluding that most of the patients visiting outpatient department of SDMCDSH, Dharwad were aware about the deadly covid-19 pandemic disease and were willing to undergo a covid test so as to prevent the spread of infection. Majority of the population have a positive attitude towards covid test and are willing to undergo the test if needed so as to prevent the spread of infection.